2008
DOI: 10.1002/ajmg.b.30637
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine, serotonin, and nicotinic gene polymorphisms with methylphenidate response in ADHD

Abstract: Gene polymorphisms of the 3' untranslated region (3'-UTR) of the dopamine transporter (DAT1), Dopamine receptor exon 3 D4 variable number tandem repeat (DRD4VNTR), nicotinic acetylcholine receptor alpha 4 subunit (CHRNA4) and serotonin transporter promoter (SLC6A4-5HTTLPR) are under consideration as potential risk factors for attention-deficit/hyperactivity disorder (ADHD). A post-hoc attempt was made to investigate the association between the allelic variations of these candidate genes and retrospective paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…A total of 16 studies published between 1999 and 2010 matched the search criteria (see Table 1), resulting in a final sample of 1572 subjects [44][45][46][47][48][49][50]52,[54][55][56][57][58][59][60] including N ¼ 799 10R homozygotes and N ¼ 773 carriers of genotypes other than 10R/10R (one study did not report genotype frequencies 53 ). The random-effects model revealed a nonsignificant summary effect size of d ¼ À 0.05 (95% confidence interval (CI): À 0.2 to 0.1, z ¼ À 0.698, P ¼ 0.52, I 2 ¼ 38.2%, 95% CI for I 2 : 11.72-91.02%, see Figure 1a), suggesting that genotype was not a significant predictor of treatment response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 16 studies published between 1999 and 2010 matched the search criteria (see Table 1), resulting in a final sample of 1572 subjects [44][45][46][47][48][49][50]52,[54][55][56][57][58][59][60] including N ¼ 799 10R homozygotes and N ¼ 773 carriers of genotypes other than 10R/10R (one study did not report genotype frequencies 53 ). The random-effects model revealed a nonsignificant summary effect size of d ¼ À 0.05 (95% confidence interval (CI): À 0.2 to 0.1, z ¼ À 0.698, P ¼ 0.52, I 2 ¼ 38.2%, 95% CI for I 2 : 11.72-91.02%, see Figure 1a), suggesting that genotype was not a significant predictor of treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…40 Although some studies have shown that the 9R allele is associated with better clinical response to methylphenidate, 27,[44][45][46][47] other studies have shown the opposite pattern [48][49][50] or have failed to observe a significant effect. [51][52][53][54][55][56][57][58][59] A recent review has summarised the literature on this topic and an early meta-analysis of six studies in childhood ADHD reported that 10R homozygotes showed poor methylphenidate response. 60 However, further studies on children and adults have appeared since then.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we focussed on a genetic variant that to our knowledge is the only one in SLC6A2 whose capacity to influence gene expression directly has been shown in biochemical assays, confirming the formation of a new transcription factor binding site. Genetic variants of candidate genes recently have been reported to influence the efficacy of pharmacological therapy in ADHD (Kooij et al 2008;Tharoor et al 2008). Recent studies investigating the association of SLC6A2 polymorphisms with response to stimulant medication reported differing results Song et al 2011;Lee et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Different polymorphisms concerning the dopaminergic, serotonergic and noradrenergic systems were studied extensively and some of them seem to be related to ADHD [38][39][40][41][42] or correlated with the response to stimulant treatment [43,44]. However, polymorphisms of genes responsible for neuronal differentiation in early stages of development like Nurr1 (NR4A2) failed to be associated with ADHD [45].…”
Section: Adhd Pathophysiologymentioning
confidence: 97%